College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.4 - Average Rate of Change of a Function - 2.4 Exercises - Page 224: 12


(a) $-1$ (b) $-\frac{1}{3}$

Work Step by Step

We are given: $r(t)=3-\frac{1}{3}t$, $t=3, t=6$ (a) We calculate the net change: $r(6)-r(3)=[3-\displaystyle \frac{1}{3}(6)]-[3-\frac{1}{3}(3)]=1-2=-1$ (b) We calculate the average rate of change: $\displaystyle \frac{r(6)-r(3)}{6-3}=-\frac{1}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.